DETERMINAN DAYA SAING WISATA KULINER NGERANGAN KLATEN - Agusetyaningrum, Theresia; Sumastuti, Efriyani; Violinda, Qristin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study began because the level of visits to Ngerangan Klaten culinary tourism was less than other culinary tours in Klaten Regency and the findings that the variables that determined competitiveness obtained different results which then led to the formulation of the problem of